Tofacitinib for refractory interstitial lung diseases in anti-melanoma differentiation-associated 5 gene antibody-positive dermatomyositis - Kurasawa, Kazuhiro; Arai, Satoko; Namiki, Yumeko; Tanaka, Ayae; Takamura, Yuta; Owada, Takayoshi; Arima, Masafumi; Maezawa, Reika (Rheumatology (Oxford, England), 2018)
Abstract Objective We aimed to determine the outcome of combination therapy with tofacitinib (TOF) in a case series of refractory rapidly progressive interstitial lung disease (ILD) associated with anti-melanoma differentiation-associated 5 gene (MDA5) antibody-positive (Ab+) DM. Patients who had poor prognostic factors and failed to respond to immunosuppressive therapy were selected for TOF treatment. Methods Five patients with anti-MDA5 Ab+ DM-ILD who failed to respond to triple therapy with high dose glucocorticoids, CSA and CYC were given additional TOF (10 mg/day). To identify the poor prognostic factors, data from 15 consecutive patients (seven survived and eight died) with anti-MDA5 Ab+ DM-ILD before induction of TOF were analysed. Results Three poor prognostic factors were identified: serum ferritin level >1000 ng/ml before therapy; ground-glass opacities in all six lung fields before therapy; and worsening of pulmonary infiltrates during therapy. All six patients who had all of the three factors and received triple therapy died before TOF therapy. There were five patients who had all of the three prognostic factors and failed to respond to triple therapy, but were able to receive the combination therapy with TOF; among them, three survived and two died. The survival rate of patients who received TOF was significantly better than that of the historical controls with immunosuppressive therapy before TOF. The patients who received TOF experienced complicated adverse events, particularly viral infection. Conclusion Combination therapy with TOF might have the potential to control refractory anti-MDA5 Ab+ DM-ILD.